Gleaming English game for youth, an android-based game for English literacy improvement: research and development - Sari, Hesty Puspita; Primasari, Yusniarsi; Supriyono, Supriyono; Herminingsih, Dwi Ima (Intelektual Pustaka Media Utama, 2026)
The integration of educational content with interactive technology in the digital age offers a promising avenue to address literacy challenges. This study primarily presents the development of an Android-based game, gleaming English game for youth (GEMOY), aimed at enhancing English literacy among secondary English as a foreign language (EFL) learner. The game is designed to merge engaging gameplay with educational objectives, specifically targeting improvements in English literacy. The research involved 50 secondary EFL learners and 4 teachers in a needs analysis interview, alongside 3 experts for the validation of materials and media. Employing the research and development (RD) methodology, the study yielded high content validity index (CVI) scores of 0.9 for educational accuracy, 1.0 for relevance, and 0.85 for clarity, indicating strong alignment with educational standards and appropriateness for the target demographic. These validation results highlight GEMOY’s potential to substantially support learners by providing an interactive and enjoyable learning experience. The game’s capacity to engage students while addressing critical literacy skills suggests it could contribute to more effective learning outcomes and the overall enhancement of language abilities. Future research should focus on expanding the evaluation of GEMOY’s effectiveness through empirical studies that assess its impact on actual learning outcomes.